New Hybrid Conjugate Gradient Method with Global Convergence Properties under Exact Line Search - Salih, Yasir; Mamat, Mustafa; Rivaie, Mohd; Abashar, Abdelrhaman; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
Conjugate Gradient (CG) method is a very useful technique for solving large-scale nonlinear optimization problems. In this paper, we propose a new formula for Bk , which is a hybrid of PRP and WYL methods. This method possesses sufficient descent and global convergence properties when used with exact line search. Numerical results indicate that the new formula has higher efficiency compared with other classical CG methods.